Attributions causales des étudiants en matière de réussite à l'université - Xavier Massart; Marc Romainville (Nantes Université, 2019)
Since higher education has developed many success-promoting schemes for first-year students, it is often regretted that these schemes are underused and that the students "who need them the least" are those who participate the most. This is particularly the case with the formative and early evaluation system introduced in this paper, which enables students to identify and fix their shortcomings as regards prerequisites. Though a significant correlation between mastery of these prerequisites and success at the end of the year has been established, too few students, from teachers' point of view, decide to take part in activities dedicated to prerequisites consolidation after having taken the tests. It is therefore essential to better understand the mechanisms that lead students to take advantage of these success-promoting schemes or not. This paper analyzes this question with respect to attributional theory: what do students feel spontaneously about the importance of prerequisites for success? What are the factors (real level of mastery of prerequisites, gender...) that are related to these attributions? The article ends with possible educational solutions that the results suggest.